Management consulting and audit in modern Russia ("Journal "U". Economy. Management. Finance.", 2018)
This article describes the basic principles of management consulting and audit, considers theoretical approaches to concepts. The demand for consulting and audit services in the Russian Federation is analyzed. The reasons of the unstable situation of domestic firms are also discussed in the article.